2009
DOI: 10.1111/j.1872-034x.2008.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PI3K/PTEN/AKT/mTOR pathway in invasion and metastasis in hepatocellular carcinoma: Association with MMP‐9

Abstract: Aim:To investigate the status of Phosphatidylinositol 3-kinase (PI3K)/PTEN/AKT/mammalian target of rapamycin (mTOR) pathway and its correlation with clinicopathological features and matrix metalloproteinase-2, -9 (MMP-2, 9) in human hepatocellular carcinoma (HCC).Methods: PTEN, Phosphorylated AKT (p-AKT), Phosphorylated mTOR (p-mTOR), MMP-2, MMP-9 and Ki-67 expression levels were evaluated by immunohistochemistry on tissue microarrays containing 200 HCCs with paired adjacent noncancerous liver tissues. PTEN, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
258
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(272 citation statements)
references
References 28 publications
11
258
0
3
Order By: Relevance
“…Previous studies have demonstrated that p21 inhibits DNA synthesis and results in a delay in the G1–S transition in the regenerating liver 28, 29. Meanwhile, Pten represses the AKT/PI3K signalling cascade, functioning as a regeneration suppressor 30, 31, 32. Indeed, we found that the loss of miR‐17~92 noticeably reduced AKT phosphorylation in the female mice, particularly at 24 and 36 hrs post‐operation (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies have demonstrated that p21 inhibits DNA synthesis and results in a delay in the G1–S transition in the regenerating liver 28, 29. Meanwhile, Pten represses the AKT/PI3K signalling cascade, functioning as a regeneration suppressor 30, 31, 32. Indeed, we found that the loss of miR‐17~92 noticeably reduced AKT phosphorylation in the female mice, particularly at 24 and 36 hrs post‐operation (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Invasion and metastasis are two fundamental properties, which determine the prognosis of the HCC patients [4,5] . Many signaling pathways are thought to be involved in the development and invasion of HCC, including the MAPK pathway [6,7] , phosphatidylinositol-3 kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway [8][9][10] , the wnt/beta-catenin pathway [9,11] , hepatocyte growth factor/c-MET pathway [12,13] , hedgehog (Hh) signaling pathway, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-9 (MMP-9 or gelatinase-B) is mostly associated with tumor migration, invasion and metastasis for various human cancers [10,47,48] . The Hh signaling pathway up-regulates cell migration and invasion in human gliomas and in pancreatic cancer by increasing the expressions of MMP-9 [49,50] .…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that PPARγ activation exerts an inhibitory effect on tumor growth by activating the tumor suppressor gene PTEN (10,11). In addition, several studies have also indicated that PTEN has a tumor suppressor role via regulating a series of factors, including MMP-2 (11,13,14).…”
Section: Pparγ Activation Regulates Mmp-2 Expression Through Ptenmentioning
confidence: 99%
“…In addition, Farrow et al (10) reported that the selective PPARγ agonist RGZ enhanced the expression of phosphatase and tensin homolog (PTEN) in pancreatic cancer AsPC-1 cells and inhibited AKT phosphorylation, while application of the PPARγ inhibitor GW9662 suppressed PTEN expression, suggesting that PPARγ ligands attenuate pancreatic cancer cell growth via inhibiting phosphoinositide 3-kinase (PI3K) activity through upregulating the expression of the tumor suppressor gene PTEN. PTEN was identified in 1997 as a tumor suppressor gene closely associated with cancer (11) w. It is important in tumor cell apoptosis and migration and is the main component of signaling pathways that control cell cycle initiation and exit, promote differentiation, initiate repair and regulate apoptosis (11). Therefore, PPARγ activation may possibly regulate the expression of MMPs through PTEN and thereby inhibit the invasion of pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%